(untitled) (Research, Society and Development, 2021)
Despite various initiatives, teenage pregnancy, sexually transmitted diseases and abortion are still common among school-age adolescents, with substantial gaps in knowledge about reproductive and sexual health among school-age adolescents, making it essential to review the teaching and learning resources available. . Therefore, the aim of this study was to identify contributions in sexual education to prevent teenage pregnancy in the context of school health available in the scientific literature. This is an integrative literature review. The search for scientific productions was carried out on the basis of PubMed® and Educational Resources Information Center. Articles published between January 2016 and December 2020, with full text, abstract available and in Portuguese or English, were selected. The search was mediated by the keywords in English: “Sex Education” AND “School Health” AND “Teenage Pregnancy”. Randomized clinical trials and evaluation studies of applied or school-based intervention programs were prevalent, which, in general, showed significant positive results in relation to the comparison mechanisms (control or pre-intervention), for the different outcomes related to the prevention of teenage pregnancy, with the exception of the baby simulator-based program, in which there was no significant reduction compared to controls for the pregnancy outcome before the age of twenty. It was concluded that sexual health education programs in the school context have predominantly aligned with measures to delay sexual initiation and or sexual protection. These programs have become an effective tool for health promotion, because through educational actions students have the opportunity to be exposed to a repertoire that favors the mitigation of health risk factors and improves their quality of life.